Anti-mycobacterial activity of Piper longum L. fruit extracts against multi drug resistant Mycobacterium Spp. - Chandan Singh,; Santosh K. Singh,; Gopal Nath,; N.P. Rai, (International Journal of Phytomedicine, 2011)
A long tradition of using pepper as to fight against several ailments by the local tribal people is still in the practice, in many parts of the rural India. So utilizing this tribal knowledge base for this highly medicinal plant, an attempt was made to isolate some novel natural bioactive compounds with potential activity against multidrug resistant (MDR) Mycobacterium. A bioassay guided fractionation of Pippali (Piper longum L.) was performed in five different organic solvents and their activities were monitored against different pathogenic bacteria including MDR Mycobacterium. Different fractions were screened for the bioactivity against Mycobacterium, and the structure of bioactive compound was characterized with H1 and C13 NMR. An ethyl acetate fraction of Pippali extract was found active against M. smegmatis (3000µg ml-1) and M. tuberculosis (39 µg ml-1). It also shows very significant activity against other bacterial strains like E.coli (152 µg ml- 1), Staphylococcus aureus (14 µg ml-1), Salmonella typhi (180 µg ml-1), Enterococcus faecalis (15 µg ml-1), and Pseudomonas aeruginosa (52 µg ml-1). This fraction of ethyl acetate was then purified and characterized as piperine [5-(1, 3-benzodioxol-5-yl)-1-piperidin-1- ylpenta-2,4-dien-1-one], a well known alkaloid from this plant. Bioactivity guided fractionation concludes that Piperine is the only active ingredients in various fractions of fruit extract evaluated for antibacterial activity. Fraction having piperine has significant activity against multi drug resistant strains of Mycobacterium spp. than other purified fractions of fruit extract. The current finding encourages us to develop new alternative medicine that includes piperine alone and/or in combination with other drugs to fight against the drug resistance among Mycobacterial strains.